Ideologia płci w jednojęzycznych słownikach języka polskiego - Dennis Scheller-Boltz (Postscriptum Polonistyczne)
The article discusses the relation between lexicography and ideology. It proves that the monolingual Polish language dictionaries are designed according to the ideology of gender and that gender stereotypes can take different forms in dictionaries. The dictionaries not only reflect, but also preserve social and cultural values and rules. The analysis leads to the question, how should the ideology of gender be presented in the future, in order to avoid stereotyping?